Rozwój zawodowy nauczycieli Gimnazjum w Barcicach a ich poczucie satysfakcji z pracy dydaktyczno - wychowawczej - Gawlak-Baszczyn, Maria (My University, 2012)
Wybór tematyki pracy był podyktowany moim zainteresowaniem reformą polskiego systemu edukacyjnego. Analiza kolejnych etapów reformy szkolnictwa pozwoliła na ich ocenę w kontekście wymogów stawianych nauczycielom. Praca obejmuje zespół zagadnień dotyczących rozwoju zawodowego nauczycieli uczących w Gimnazjum w Barcicach. Analiza form doskonalenia zawodowego pozwoliła ustalić w części badawczej pracy zespół czynników rzutujących na poczucie satysfakcji nauczycieli z wykonywanej pracy dydaktycznej oraz wychowawczej. Jako metodę badań zastosowano ankietę, a narzędziem badawczym stał się kwestionariusz ankietowy. Ustalenia poczynione w toku badań pozwoliły zdiagnozować częstotliwość uczestnictwa respondentów w różnych formach doskonalenia, ustalić formy najbardziej popularne wśród nauczycieli oraz zweryfikować prawdziwość postawionych hipotez dotyczących źródeł satysfakcji nauczycieli z wykonywanej pracy.

The main objective of this study is to examine and evaluate the problem of reform in Polish education at its various stages and looking at its requirements towards teachers. My personal interest in the reform of the Polish educational system has been the main source of inspiration for choosing this subject matter. This work presents a number of issues connected with continuous professional development of teachers, on the example of a lower secondary school-Gymnasium in Barcice. Its research part introduces and analyses different forms of the professional development process and its ultimate goal was to establish a set of factors influencing teachers satisfaction, both in their teaching and educational work. The research method used was a survey with a questionnaire survey deployed as a research technique. obtained in the course of the study have been used in a number of ways. First of all it allowed for determining the frequency of the respondents participation in various forms of professional development and completing a list of the forms popular among teachers .The results were then used to verify the correctness of the hypotheses made about the sources of teachers satisfaction in their work.
Professional development of teachers in Gymnasium in Barcice concerned to experience of satisfaction of teaching and educational work
Keywords: praca dydaktyczno – wychowawcza; rozwój zawodowy; formy doskonalenia; poczucie satysfakcji; kompetencje zawodowe; ankieta; teaching and educational activities; professional development; forma of professional development; professional competencies; survey